EARLY VASCULAR AGEING IN PATIENTS WITH HYPOPARATHYROIDISM. (June 2022) - Fabbri, Saverio; Boutouyrie, Pierre; Khettab, Hakim; Maruani, Gérard; Houillier, Pascal; Bruno, Rosa Maria
Abstract : Objective: Hypoparathyroidism may induce arterial damage, but underlying mechanisms are not well established. Few papers have addressed the topic, reporting an increase in central values and in carotid intima-media thickness [1][2]. The aim of this study was to determine the presence of early vascular ageing signs in large and small arteries. Design and method: 17 patients affected by hypoparathyroidism and 17 healthy controls (matched for age, sex, blood pressure and risk factors) were studied to obtain carotid-femoral PWV, carotid and digital intima-media thickness and stiffness bystandard and ultta-high frequency ultrasound respectively. In the patients affected by hypoparathyroidism, complete calcium-phosphorus metabolism blood tests were taken. Results: carotid distensibility was significatively lower in the patients group (18, 7 ± 6.0 vs 39, 4 ± 10, 5 (kPa at(-1)) p < 0.001), with a marked increase in carotid stiffness (7, 6 ± 1, 3 vs 5, 3 ± 0, 9 m/s, p < 0.001). No significant difference was reported in PWV and central pressure among the groups. A reduced digital artery diameter was present (mean diameter 0, 8 ± 0, 1 vs 1, 0 ± 0, 2 mm p = 0.005), with a reduced stiffness (5, 6 ± 2, 5 vs 9, 2 ± 4, 9 m/s p < 0.05). A positive correlation between carotid artery stiffness and Calcium – Phosphorus product was found in the patients group (r = 0.538 p = 0.031). Conclusions: Hypoparathyroidism is characterized by increased carotid artery stiffness. Digital stiffness (UFHS) is paradoxically reduced (possibly as compensatory mechanism), with hypotrophic emodelling. Our data support altered calcium-phosphorus metabolism as mechanism of arterial damage.